Integrative redescription of the enigmatic monotypic alpine pill millipede genus Simplomeris Verhoeff, 1936 (Glomerida, Glomeridae, Haploglomerinae) - Wesener, Thomas (Zootaxa, 2022)
The European pill millipedes (Glomerida) are especially rich in species and genera of enigmatic status, which have been neither reviewed nor revised since more than 70 years. One of these genera is Simplomeris Verhoeff, 1936 with its single species S. montivaga (Faës, 1902), a high-altitude endemic only known from <5 collection events in the Simplon Valley and the Aletsch Glacier, southern Switzerland. Being one of only a handful of genera in the subfamily Haploglomerinae, distributed in Europe and SE Asia, its morphology is of greater interest in a future phylogenetic sorting of the Glomerida. Fresh material, which was encountered by the author 10 years ago from both known localities, allows here a redescription of this rarely encountered genus. Aside from the first photograph of a living specimen, scanning electron microscopy and genetic barcoding of the COI gene have been conducted. Morphologically, the telopods of Simplomeris resemble those of Haploglomeris Verhoeff, 1906 from the eastern Alps and confirm the present position in the Haploglomerinae. Genetically, Simplomeris belongs to the Glomeris klugii Brandt, 1833 species-group and is particularly close to high-altitude endemics from the southwestern and Bergamasque Alps, especially G. primordialis Verhoeff, 1930, G. transalpina Koch, 1836, and G. oropensis Verhoeff, 1934. Genetic barcoding data confirm the three colour varieties of S. montivaga, S. montivaga var. montivaga Verhoeff, 1936 syn. nov., S. montivaga var. simplonensis Verhoeff, 1936: syn. nov., S. montivaga var. berisalensis Verhoeff, 1936 syn. nov. to be just that, and all three are formally synonymized under S. montivaga.